Особливості гідрологічного режиму та руслові процеси на річці Ільця (басейн Чорного Черемошу) - Костенюк, Людмила Володимирівна; Kosteniuk, Liudmyla (Чернівецький національний університет імені Юрія Федьковича, 2020)
Проаналізованоособливості гідрологічного режиму та руслові процеси р.Ільця (лівий доплив р.Чорний Черемош), на основі даних регулярних спостережень та під час експедиційного виїзду у червні 2019 року. Представлено схеми басейнового розподілу та геоморфологічного районування досліджуваного об’єкту, криві зв’язку витрат води і рівнів Q=f(H), графіки ходу максимальних, середніх та мінімальних рівнів води, а також поперечні перерізи на ключових ділянках.
Features of the hydrological regime and channel processes on the Iltsya river (Chorny Cheremosh basin)
This publication analyzes the features of the hydrological regime and channel processes of the Iltsya River, based on regular observations and during the expedition trip in June 2019.The schemes of basin dis tribution and geomorphological zoning of the studied object, curves of connection of water consumption and levels Q = f (H), graphs of the course of maximum, average and minimum water levels, and also cross sec tions on key sites are presented in the work. Conditions of channel formation of natural watercourses are a complex and multilateral process which is closely connected with natural features of the territory of their basin.The main factors of the natural channel process are the geological structure of the area, sediment flow and grain size. These factors are key, however, the processes of channel formation are also influenced by additional factors that are temporary or local in nature. At the same time, we should not forget about the influence of the anthropogenic factor, the results of which for the basins of small rivers can sometimes even dominate for some time over the main ones men tioned above. All these factors not only affect the channel process, but also difficult to interact with each other. The geological structure, including the lithology of rocks, as well as the relief of the territory, have a di rect impact on the shape of the valley, the longitudinal profile, the composition of channel-forming sedi ments, and hence the stability of the channel. Water runoff is the main active factor that depends on the hy drological regime of the river and determines its water content and size. The nature of the sediments and their regime is a factor that determines the rate and direction of vertical and horizontal deformations of the channel.
Keywords: гідрологічний режим, стік води, стік наносів, руслові процеси, геоморфологічне районування, поперечний переріз